2016
DOI: 10.1210/jc.2016-2385
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes After Very-Low-Calorie Ketogenic Diet in Obesity Evaluated by 3 Standardized Methods

Abstract: The VLCK diet-induced weight loss was mainly at the expense of FM and visceral mass; muscle mass and strength were preserved. Of the 3 body composition techniques used, the MF-BIA method seems more convenient in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(135 citation statements)
references
References 39 publications
14
117
0
4
Order By: Relevance
“…However, most of these studies were performed using animal models of hepatocellular carcinoma (HCC) and followed a high‐fat diet before the administration of a chemical carcinogen, whereas few studies had evaluated the potential of weight loss in preventing the carcinogenic risk associated with obesity . Weight loss therapies are effective in improving most of the obesity‐associated phenotypes, such as body fat mass, lipid and glucose metabolism, and biomarkers of inflammation and oxidative stress . However, whether these beneficial effects can reduce the risk of the liver injury that leads to hepatocarcinogenesis remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies were performed using animal models of hepatocellular carcinoma (HCC) and followed a high‐fat diet before the administration of a chemical carcinogen, whereas few studies had evaluated the potential of weight loss in preventing the carcinogenic risk associated with obesity . Weight loss therapies are effective in improving most of the obesity‐associated phenotypes, such as body fat mass, lipid and glucose metabolism, and biomarkers of inflammation and oxidative stress . However, whether these beneficial effects can reduce the risk of the liver injury that leads to hepatocarcinogenesis remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, interest in the identification of natural remedies to prevent and control obesity with few or no adverse reactions has grown. Recent studies have indicated that some diets and natural compounds, such as the Mediterranean diet and capsaicin, show counteractive effects on obesity [12, 13]. Cinnamaldehyde (CA), a pungent component of cinnamon (bark of Cinnamomum cassia ), is widely used in drugs, food and spices.…”
Section: Introductionmentioning
confidence: 99%
“…The multidisciplinary model of BED intervention based on person-centered care leads to greater self-confidence and self-esteem, causing changes in eating behavior and reducing compulsive episodes [35,36].…”
Section: Resultsmentioning
confidence: 99%